2011
DOI: 10.1088/0957-4484/22/38/385201
|View full text |Cite
|
Sign up to set email alerts
|

A precise optical determination of nanoscale diameters of semiconductor nanowires

Abstract: Electrical and optical properties of semiconducting nanowires (NWs) strongly depend on their diameters. Therefore, a precise knowledge of their diameters is essential for any kind of device integration. Here, we present an optical method based on dark field optical microscopy to easily determine the diameters of individual NWs with an accuracy of a few nanometers and thus a relative error of less than 10%. The underlying physical principle of this method is that strong Mie resonances dominate the optical scatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 25 publications
0
37
0
Order By: Relevance
“…Indeed, it has been shown that even a small tapering of semiconductor NWs affects the scattering resonances. 23,32 In the present case the tapering of the NW is about 1 magnitude higher (i.e., the change of the radius is about 10 times higher within approximately the same length) than that of the tapered GaAs NW studied in ref 23. A more fitting description of these resonances is that of volume resonances determined by the complete three-dimensional structure.…”
Section: Nano Lettersmentioning
confidence: 51%
See 1 more Smart Citation
“…Indeed, it has been shown that even a small tapering of semiconductor NWs affects the scattering resonances. 23,32 In the present case the tapering of the NW is about 1 magnitude higher (i.e., the change of the radius is about 10 times higher within approximately the same length) than that of the tapered GaAs NW studied in ref 23. A more fitting description of these resonances is that of volume resonances determined by the complete three-dimensional structure.…”
Section: Nano Lettersmentioning
confidence: 51%
“…It has been shown earlier that this is a good approximation for the light scattering of individual semiconductor NWs. 21− 23 The radii of the investigated NWs are smaller than 80 nm. These NWs support only a single mode, the so-called fundamental mode.…”
mentioning
confidence: 99%
“…1a-c) 26 . We find that light absorption in single standing nanowires is more than one order of magnitude more efficient than is predicted from the Lambert-Beer law.…”
mentioning
confidence: 99%
“…For low-absorbing materials (for example, indirect bandgap materials such as silicon), waveguiding effects plays a key role 23,24 , whereas highly absorbing semiconductors (such as direct-bandgap GaAs) exhibit resonances that increase the total absorption several times. Nanowires lying on a substrate also exhibit such resonances, often described by Mie theory 25,26 , although the total absorption rate is significantly lower 27,28 . Even though the optical absorption of nanowires arranged in an array has been shown to be far more complex than in thin films, nanowire vertical arrays currently seem to be the most reasonable device proposal.…”
mentioning
confidence: 99%
“…[12][13][14]17,[20][21][22][23][24][25][26][27] For example, absorption or scattering cross sections have been estimated qualitatively, 17,[20][21][22][23] while in other works wavelength-dependent photocurrent measurements performed on single NW PV devices were used to assign quantitatively the resonances of NW optical cavities. [13][14][15] Concurrent with experiments, numerical and analytical calculations of the resonant modes and key optical figures of merit (e.g.…”
mentioning
confidence: 99%